IMPLEMENTASI KLINIK LITERASI SEBAGAI PENGUATAN KEMAMPUAN BELAJAR MEMBACA SEKOLAH DASAR - Jeni Rahma Dani; Asrilda Aeni; Siska Safitri; Nur vivin; Ferdy Adrista Wiguna; Syafruddin Muhdar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article aims to analyze the implementation of literacy clinics as a strategic approach to strengthening elementary school students’ reading skills within instructional contexts that remain largely uniform and insufficiently responsive to diverse learning needs. The study employs a Systematic Literature Review design combined with a descriptive qualitative approach to develop a comprehensive understanding of literacy clinic practices, drawing on scholarly publications indexed in Google Scholar from 2016 to 2026 that were selected based on relevance and methodological rigor. The findings indicate that literacy clinics function not merely as remedial programs for struggling readers, but also as diagnostic frameworks capable of identifying specific learning barriers. Through structured and flexible interventions, these programs contribute to improvements in reading accuracy, text comprehension, and students’ active engagement in the learning process, while also encouraging a shift in teachers’ pedagogical practices toward more adaptive, reflective, and student-centered approaches. Furthermore, the effectiveness of literacy clinics is closely linked to teachers’ diagnostic competence, consistency in implementation, and the presence of a supportive school environment, suggesting that literacy clinics should be positioned not only as remedial interventions but also as transformative pedagogical models that foster the sustainable development of foundational literacy skills in elementary education